(untitled) (City: History, Culture, Society, 2023)
The purpose of this study was to determine the image of the Donbas cities carried by children who have become forced migrants. The article is based on interviews with individuals under the age of 18 in 2014 who were forced to flee their homes due to the conflict in Donbass. These interviews were conducted primarily in 2020 and 2021. The interviewees cannot return to their cities for various reasons; for some, attempting to cross the border between the so-called LPR and DPR could land them in prison due to the status or public standing of their families. It is important to note that frequently the child did not have the chance to say goodbye to the parental home because the departure was planned for several days or weeks in advance. The article analyzes, from the perspective of the psychology of overcoming a traumatic experience, how the inability to return and the absence of a farewell ceremony affect the current state of a person. It is important for a person to revisit places associated with his childhood and his family’s history at various stages of his life. Such locations include ancestral graves, parental homes, and others associated with significant life events. This situation is complicated by the fact that many respondents’ ancestors, such as grandfathers and grandmothers, chose to remain in territory not under Ukrainian government control. The inability to "say goodbye" traumatizes the psychological state of a person who has been deprived of his roots. What will happen if the images of immigrants and locals collide, how can a potential conflict be avoided, and what role can it play in the reintegration process? The article is relevant to the reconstruction of the cities of Donbass, which were previously in uncontrolled territory, because it raises the issue of image conflict and seeks a solution to this issue.